NILAI KEJUANGAN LASKAR SABILILLAH MALANG DAN PEWARISANNYA - Najib Jauhari (Jurnal Sejarah dan Budaya, 2013)
Abstract. The national life in Early period of Indonesia Independence was marked by many physical struggle for defending of state sovereignty. It is known as Independence War Period (1945-1949). The Troop of Sabilillah is one of struggle organizations in war of independence era. There are two problems studied in this article, namely development of Troop Sabilillah and values of struggle and its heritage. Method of study is based on three main data sources, namely interview to the witness, observation of artifacts and literature study. The results of study are the development of Troop Laskar Sabilillah based on Resolution of Jihad Nahdlotul Ulama’ and Decision of Masyumi Conggres, and the values of national spirit (nationalism) are created on heritage forms of Mosque Monument and Education Foundation of Sabilillah Malang (Yayasan Pendidikan Sabilillah Malang)